Oświeceniowe rozważania o eposie. Dyskusja wokół Pułtawy i Jagiellonidy - Kwiatkowska, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
Literary polemics are a very characteristic phenomenon of eighteenth century culture. Some of the polemics refer to the essential problems of culture, while others, such as the analysed discussion on “Jagiellonida” and “Pułtawa”, are critical in nature. The reviewers criticise the two unsuccessful epics, however, they also touch upon the important issues concerning this genre. Who should be the protagonist in epic literature? How to combine realism with fantasy fiction? Which classical authors should be imitated? The answers to these questions are sought by the theoreticians of Enlightenment literature and the participants in this argument. A reconstruction and juxtaposition of their opinions are presented in this article.